International Migration and the Welfare State: Asian perspectives - Gaston, Noel; Rajaguru, Gulasekaran (Routledge, 2013)
Immigration is a controversial topic in Australia and some of its Asian neighbours. Given the potential impact on native welfare, such as effects on relative wages and unemployment, there has been political mobilisation on the immigration question. The presence of a redistributive welfare state in all major immigrant host countries creates yet another margin on which immigration affects native welfare. The focus of the paper is whether a large intake of immigrants leads to a reduction in welfare state effort. It is often argued that steady increases in immigration lead to public pressure for stricter immigration controls or for less generous publicly funded social expenditures. In terms of immigrants with similar employability and claims on the public purse to natives, it is hypothesised that the impact on welfare spending is neutral. These ideas are tested using detailed data for migration to developed countries.